(untitled) (Chemical Engineering Research Bulletin, 2011)
Polygalacturonase production by isolated fungal strains was carried out in solid state fermentation. Aspergillus niger (A. niger) and Penicillium sp EGC5 produced polygalacturonase (PG) on mixture of apple bagasse and wheat bran. The mixture of apple bagasse and wheat bran acted as a good nutrient source and substrate for the cultivation of the microorganisms and polygalacturonase produced in solid state fermentation. In this respect, it was possible to obtain polygalacturonase activity at an acceptable yield, in comparison with a typical defined medium described in the literature for polygalacturonase production. Higher titres of polygalacturonase were observed when medium was supplemented with carbon (pectin) and nitrogen ((NH4)2SO4 and peptone) sources. The maximum production of polygalacturonase was reached after 8 days cultivation. The temperature was 30°C and the relative humidity of the fermentation medium was 70%. Key words: Polygalacturonase; Aspergillus niger; Apple bagasse; wheat bran; Solid state fermentation DOI: http://dx.doi.org/10.3329/cerb.v15i1.6368 Chemical Engineering Research Bulletin 15 (2011) 1-5